Consumo colaborativo na moda: um estudo sobre as motivações e barreiras da participação em serviços de guarda-roupas compartilhados - Farah, Eva (2019)
Collaborative consumption (CC) is characterized by access, instead of ownership, to products and services and still faces challenges to gain critical mass and scale. Examples of CC have grown in recent years and gained strength in other not-so-obvious sectors, such as fashion industry. In the context of collaborative fashion consumption (CFC), there is a new business model, the fashion library, which has been gaining media attention. From this scenario, the objective of this study is to understand the barriers and motivations of participation in this new collaborative fashion consumption service. To achieve the expected results, the problem was analysed with a qualitative approach through 25 deep interviews, of which 14 with users and 11 with ex-users of this service. From the data analysis, performed using ATLAS TI software, 13 categories of motivations and 7 categories of barriers were identified. In this way, we hope to contribute to the growth of the recent literature of collaborative fashion consumption, and to provide the fashion companies with the necessary knowledge to adapt to new business models and support the growth of the specific business model of fashion library.